Strengthening student literacy about Asesmen Kompetensi Minimum (AKM) questions at MI Luqman Al-Hakim Slawi - Hasna’ Nadia Shalihah; Risris Hari Nugraha (Universitas Pendidikan Indonesia, 2023)
Literacy is still a study of unresolved issues in Indonesia. Until now, all parties are still organizing various programs to increase the literacy level of Indonesian society. An effective way to improve literacy is to start at the primary level. This service aims to strengthen the literacy level of students participating in AKM (Minimum Competency Assessment) from their understanding of AKM questions. It also aims to discover how to overcome the problems experienced by students. This service carries out a student literacy strengthening program based on understanding the AKM questions that have been worked on. So that if students find similar questions, they are expected to do it more quickly and precisely. This activity results in students needing help with AKM in literacy, such as taking a long time to read, needing to be more careful about details, and needing help answering reflection questions correctly. The obstacles in AKM in the field of numeration are the difficulty in understanding the meaning of the questions and the need for more proficiency in basic calculations. The solution to the problem above is to strengthen students' habits of reading and doing math problems because these two things are the most basic knowledge in the learning process and enhance literacy.